Berberine Attenuates Development of the Hepatic Gluconeogenesis and Lipid Metabolism Disorder in Type 2 Diabetic Mice and in Palmitate-Incubated HepG2 Cells through Suppression of the HNF-4α miR122 Pathway - Wei, Shengnan; Zhang, Ming; Yu, Yang; Lan, Xiaoxin; Yao, Fan; Yan, Xin; Chen, Li; Hatch, Grant M. (PLOS ONE, 2016)
Berberine (BBR) has been shown to exhibit protective effects against diabetes and dyslipidemia. Previous studies have indicated that BBR modulates lipid metabolism and inhibits hepatic gluconeogensis by decreasing expression of Hepatocyte Nuclear Factor-4α (HNF-4α). However, the mechanism involved in this process was unknown. In the current study, we examined the mechanism of how BBR attenuates hepatic gluconeogenesis and the lipid metabolism alterations observed in type 2 diabetic (T2D) mice and in palmitate (PA)-incubated HepG2 cells. Treatment with BBR for 4 weeks improve all biochemical parameters compared to T2D mice. Treatment of T2D mice for 4 weeks or treatment of PA-incubated HepG2 cells for 24 h with BBR decreased expression of HNF-4α and the microRNA miR122, the key gluconeogenesis enzymes Phosphoenolpyruvate carboxykinase (PEPCK) and Glucose-6-phosphatase (G6Pase) and the key lipid metabolism proteins Sterol response element binding protein-1 (SREBP-1), Fatty acid synthase-1 (FAS-1) and Acetyl-Coenzyme A carboxylase (ACCα) and increased Carnitine palmitoyltransferase-1(CPT-1) compared to T2D mice or PA-incubated HepG2 cells. Expression of HNF-4α in HepG2 cells increased expression of gluconeogenic and lipid metabolism enzymes and BBR treatment or knock down of miR122 attenuated the effect of HNF-4α expression. In contrast, BBR treatment did not alter expression of gluconeogenic and lipid metabolism enzymes in HepG2 cells with knockdown of HNF-4α. In addition, miR122 mimic increased expression of gluconeogenic and lipid metabolism enzymes in HepG2 cells with knockdown of HNF-4α. These data indicate that miR122 is a critical regulator in the downstream pathway of HNF-4α in the regulation of hepatic gluconeogenesis and lipid metabolism in HepG2 cells. The effect of BBR on hepatic gluconeogenesis and lipid metabolism is mediated through HNF-4α and is regulated downstream of miR122. Our data provide new evidence to support HNF-4α and miR122 regulated hepatic gluconeogenesis and lipid metabolism as promising therapeutic targets for the treatment of T2D.